Perilaku Keputusan Pembelian Generasi Y dan Z dalam Penggunaan E-Commerce di Masa Pasca Pandemi - Wijaya, I Gusti Ngurah Satria; Ekayasa, Made Dharma (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
In business during the post-covid-19 pandemic or the implementation of the new normal, many things can influence the behavior of purchasing decisions for a product, which is caused by factors such as: personal, social, cultural, and psychological. This transition period will leave new habits during the pandemic period. Every company must make changes in managing its business, if it wants to survive and win the competition. This study aims to analyze the comparison of changes in the purchasing decision behavior factors of generation Y and Z consumers with the use of e-commerce in the post-pandemic period. The analytical method used is the Structural Equation Modeling (SEM) technique through the use of Partial Least Squares (PLS-SEM). The results of the study stated that the comparison of results between respondents of generation Y and generation Z, there were three factors that had different results or contradictory results, namely perceptions of convenience, E-WOM, and price. Perception of convenience and E-WOM have a significant positive relationship to the purchase decision of generation Y, while price suitability does not affect the decision of generation Y in buying an item. Generation Z in making purchasing decisions really considers the price suitability factor. Meanwhile, E-WOM and perceived convenience are not considered by Generation Z. Positive emotion factors have a significant positive relationship for both Generation Y and Generation Z and perceived usefulness, security, motivation factors have a positive but not significant relationship with e-commerce purchasing decisions. in the post-pandemic